A community‐wide approach to reducing risky drinking cultures in young people in rural Australia. (25th October 2022) - Murphy, Angela; Ollerenshaw, Alison
Abstract: Objective: This study evaluated the impact of a multi‐faceted, harm minimisation program addressing youth alcohol change and risky drinking behaviours in rural Australia. The role and influence of a multi‐tiered community approach to changing alcohol cultures is examined. Setting: An alcohol culture change project for young people (12–18 years) was implemented in rural Victoria. It was informed by the Alcohol Cultures Framework, comprising community‐wide events and youth‐focused activities, co‐designed with young people. The approach aimed at maximising engagement and reducing alcohol‐related harm by targeting the shared activities and drinking practices of young people, parents and the community. Participants: Participants ( n  = 446) provided feedback specific to three key program activities for promoting alcohol change. Design: Mixed methods: Feedback sheets were collected, and interviews and focus groups were conducted with program participants. Results: Participants indicated that the program had informed their understanding of the way people in their region drink, and the social norms and practices around alcohol that encourage risky drinking. It influenced their short‐ and medium‐term reactions, learnings and activities relating to alcohol consumption. The impact of the program was greatest in adults than young people although reflective learning and some behaviour change were evident across all age groups and community clusters. Conclusion: Community‐wide health promotion events offer participants a deeper understanding of the ways in which dominant alcohol cultures inform the practices and activities of young people within a broader community context. Ensuring health promotion programs within a whole‐of‐community approach are established longer term, is recommended.